Performance of Growth, Survival Rate, and Behavioral in Seabass (Lates calcarifer) Seed Production with Artemia Enrichment using Sardinella Oil - Nisa, Andina Chairun; Ilham, Ilham; Aras, Annisa Khairani; Insani, Liga; Jatayu, Diklawati; Febrianti, Desy; Mahendra, I Gede Rezza (Journal of Aquaculture and Fish Health, 2025)
Essential nutrients for seabass (Lates calcarifer) growth can be derived from the live feed Artemia sp. Artemia sp. It is reported to contain protein levels between 40 and 55%, carbohydrate levels between 15 and 20%, and a lipid content of around 0.4%. Enrichment of Artemia sp. It is necessary to improve its nutritional value and promote seabass larval growth. Sardinella fish oil is one option for enriching Artemia sp. This study aims to determine the optimal dosage of Sardinella oil for Artemia sp. Enrichment to achieve optimal growth and survival rates in seabass (Lates calcarifer) larvae. The study employed a completely randomized design (CRD) with five treatments and three replicates. The treatments were: unenriched Artemia (K-), Artemia + 0.9 g/l Squalene Fish Oil (K+), Artemia + 1 ml Sardinella Oil (A), Artemia + 1 ml Sardinella + 1 ml Egg Yolk (B), and Artemia + 0.5 ml Sardinella Oil + 0.5 ml Egg Yolk (C). The highest absolute weight was observed in treatments A and C, both recording 2.02 g (±0.20 g and ±0.09 g, respectively). Regarding absolute length, treatments A and C also showed the highest values, measuring 1.89 cm (±0.17 g) and 1.90 cm (±0.17 g), respectively. The highest survival rate (SR) was likewise found in treatments A (34.67% ± 2.63%) and C (38.08% ± 3.89%). Based on the tested treatments, the optimal dose for seabass growth and survival (SR) was determined to be treatment C, which included 0.5 ml of Sardinella oil and 0.5 ml of egg yolk.